2017
DOI: 10.1111/1365-2478.12549
|View full text |Cite
|
Sign up to set email alerts
|

Full waveform inversion of SH‐ and Love‐wave data in near‐surface prospecting

Abstract: We develop a two‐dimensional full waveform inversion approach for the simultaneous determination of S‐wave velocity and density models from SH ‐ and Love‐wave data. We illustrate the advantages of the SH/Love full waveform inversion with a simple synthetic example and demonstrate the method's applicability to a near‐surface dataset, recorded in the village Čachtice in Northwestern Slovakia. Goal of the survey was to map remains of historical building foundations in a highly heterogeneous subsurface. The seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 67 publications
(101 reference statements)
0
34
0
Order By: Relevance
“…More recently, the existence of a beyond‐VTI anisotropy was reconfirmed (Wookey et al, ). Horizontally polarized shear waves and their superpositions propagating as Love waves had a significant impact on recent near‐surface inversions (Dokter et al, ; Pan et al, ). Typically, inversions focus on the velocity of SH waves along the horizontal axis; below we investigate which trade‐offs are irresolvable in inversions of this particular mode.…”
Section: Spectral Sensitivity Matrices and Numerical Analysis Of Tradmentioning
confidence: 99%
“…More recently, the existence of a beyond‐VTI anisotropy was reconfirmed (Wookey et al, ). Horizontally polarized shear waves and their superpositions propagating as Love waves had a significant impact on recent near‐surface inversions (Dokter et al, ; Pan et al, ). Typically, inversions focus on the velocity of SH waves along the horizontal axis; below we investigate which trade‐offs are irresolvable in inversions of this particular mode.…”
Section: Spectral Sensitivity Matrices and Numerical Analysis Of Tradmentioning
confidence: 99%
“…It also applies to other dispersive waves, which have a liner moveout. For example, Love waves also could be used in the proposed inversion (Dokter et al, 2017). The proposed method also has the potential to estimate the anisotropy of the near-surface using the difference in dispersion spectra in the inline and crossline directions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical examples (Romdhane et al 2011;Zeng et al 2011a;Bretaudeau et al 2013;Borisov et al 2017;Pan et al 2018a) have demonstrated that FWI is a promising way in quantitatively imaging near-surface structures. Applications of FWI on field data sets (Tran et al 2013;Kallivokas et al 2013;Amrouche and Yamanaka 2015;Nguyen et al 2016;Pan et al 2016b;Dokter et al 2017) have also proved the applicability as well as the high resolution of FWI for characterizing near-surface heterogeneity. Shallow-seismic FWI is an ill-posed problem and could converge toward a local minimum especially when a poor initial model is provided ).…”
Section: Introductionmentioning
confidence: 96%